ANALISIS PRODUKSI DURIAN MONTHONG DI DESA OGORANDU KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MAUTONG - Sutarni, Nani; Antara, Made; Effendy, Effendy (AGROTEKBIS, 2018)
This study aims was to determine the factors influencing the production of durianMonthong in Ogorandu village Bolano Lambunu subdistrict Â Parigi Moutong regency and was conducted in October-November2016.Respondents of this study were durian Monthong farmers selected from a population of 215 farmers. Data were analyzed using the production function Cobb â Douglas analysis.The value of F-countedwas 246.397)>F-table (Î± 1% = 1.597) indicated that the independent variables such as plant producing number (X1), labor (( ), urea fertilizer ( ), NPK fertilizer ( ), and plant age ( ) simultaneously affect the plant production.Â The t test also shows that the plant producing number, the labor, the urea fertilizer, and the NPK fertilizer variables partially affected the plant production with the t-counted of 17.857, 11.411, 9.857, and 9.374, respectively, at the significant level of 0.00<0.01.Â The only independent variable that has no significant effect was the plant age.Â Keywords: Monthong durian and Production analysis.